2015
DOI: 10.1177/1477370815571948
|View full text |Cite
|
Sign up to set email alerts
|

The public sense of justice in Scandinavia: A study of attitudes towards punishments

Abstract: Crime policy is increasingly legitimized by reference to the public sense of justice. A research project has therefore been conducted in all five Scandinavian countries in order to examine the public's views on punishment. These views have been examined by means of simple questions in telephone interviews, by vignettes in postal questionnaires, and by focus groups having seen a film of a mock trial. The results show that, when asked simple questions, the public want stiffer sentences. In their assessments of t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
51
0
4

Year Published

2018
2018
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 35 publications
(58 citation statements)
references
References 20 publications
1
51
0
4
Order By: Relevance
“…This result confirms many previous observations (see e.g. Balvig et al 2015;Roberts and Hough 2011), so it does not merit further attention here. Our second question was about information included in case vignettes and its connection to sentence decisions.…”
Section: Discussionsupporting
confidence: 93%
See 4 more Smart Citations
“…This result confirms many previous observations (see e.g. Balvig et al 2015;Roberts and Hough 2011), so it does not merit further attention here. Our second question was about information included in case vignettes and its connection to sentence decisions.…”
Section: Discussionsupporting
confidence: 93%
“…The impact of education on mitigating punitive attitudes also seems to be connected to the fact that people generally have quite poor knowledge about crime and the workings of the criminal justice system . Many studies have shown that the punitive attitudes of people decrease in severity the more they know about how the criminal justice system operates and about the alternatives for punishment (Balvig et al 2015;Gelb 2008;Roberts et al 2012). One possible reason for this is that the key source of information about such matters for ordinary people is the media, which often highlights exceptionally serious crime cases and in a way that prejudges the punishments handed out for crimes (Roberts and Doob 1990).…”
Section: Attitudes To Punishment and Knowledgementioning
confidence: 99%
See 3 more Smart Citations